Intensity dependent estimation of noise in microarrays improves detection of differentially expressed genes - Köstler Wolfgang J; Amir Amnon; Zeisel Amit; Domany Eytan (BMC Bioinformatics, 2010)
Abstract Background In many microarray experiments, analysis is severely hindered by a major difficulty: the small number of samples for which expression data has been measured. When one searches for differentially expressed genes, the small number of samples gives rise to an inaccurate estimation of the experimental noise. This, in turn, leads to loss of statistical power. Results We show that the measurement noise of genes with similar expression levels (intensity) is identically and independently distributed, and that this (intensity dependent) distribution is approximately normal. Our method can be easily adapted and used to test whether these statement hold for data from any particular microarray experiment. We propose a method that provides an accurate estimation of the intensity-dependent variance of the noise distribution, and demonstrate that using this estimation we can detect differential expression with much better statistical power than that of standard t-test, and can compare the noise levels of different experiments and platforms. Conclusions When the number of samples is small, the simple method we propose improves significantly the statistical power in identifying differentially expressed genes.